Effectiveness of Proline (B), Humic Acid (H), and Salinity (S) on the Vegetative Indicators and Chemical Properties of Wormwood Plants - Hamza, Manar Abdullah; Mohammed, Ahmed Adnan; Mohammed, Dalal Fattah; Abdalla, Hero Farman; Yaseen, Muzhir Saadallah (American Journal of Botany and Bioengineering, 2026)
This study was conducted during the 2023 summer season In the wooden pergola belonging to the Department of Horticulture and Landscape Engineering - College of Agriculture - Tikrit University The aim was to study the effect of proline, humic acid, and salinity on the vegetative indicators and chemical properties of the wormwood plant. The results of this work accorded that spraying proline at a concentration of 200 mg/L significantly affected all the studied vegetative and chemical characteristics in this experiment, except for the percentage of dry matter. The addition of humic acid had a positive role in most of the traits studied in this study, as the 3 g L-1 level significantly increased plant height, number of leaves, nitrogen, phosphorus, potassium and carbohydrates. The effectiveness of sodium chloride (S) had a significant effect on wormwood plants, exceeding the 10 g/L level in nitrogen, phosphorus, potassium, and carbohydrates. The interfere between (B) treatment(200 mg L⁻¹) and (S) treatment (10 g L⁻¹) significantly affected all chemical properties except phosphorus. vegetative properties not affected by interfere between (B) treatment and (S) treatment. The interfere between (B) treatment (200 mg L⁻¹) and the control treatment also had a significant effect.